Health Inequalities in Under-Five Mortality: An Assessment of Empowered Action Group (EAG) States of India - Sarvesh Kumar; Damodar Sahu; Amit Mehto; Ravendra Kumar Sharma (Journal of Health Economics and Outcomes Research)
**Background:** The effect of childhood well-being programs is commonly interconnected with a change in mortality trends. The proportion of disparity shows that inequality in child mortality is more collective in the similarly evolved states than the poorer states in India.